Kajian Timbulan dan Komposisi Sampah di Kampus Institut Teknologi Nasional Bandung (Itenas) - Gumilar, Geany Sharah; Ainun, Siti (Jurnal Teknologi Lingkungan, 2021)
ABSTRACT Educational institutions are places to conduct research and innovation to improve the quality of an independent environment. This study aims to determine the amount of waste generation and composition of institutions, especially the Bandung National Institute of Technology (Itenas). The sampling method is based on SNI 19-3964-1994 by measuring the production and composition of waste for eight consecutive days. The study results obtained an average generation of Itenas waste of 0.015 kg/m2/day or 0.156 kg/person/day in units of weight and 0.242 liters/m2/day or 2.446 liters/person/day in units of volume. The composition of Itenas waste is dominated by organic waste by 50.78%, which consists of food scraps and leaves, while other waste compositions include 14.09% plastic; 4.54% cardboard; 2.33% paper; 1.93% fabric; 1.21% glass; 0.08% cans; 0.03% metal; and 24.99% residue or other waste. The highest activities that produce organic waste in Itenas are canteen activities, while the Student Center (SC) activities make the highest amount of recyclable waste. Keywords: institutional solid waste, solid waste generation, waste composition, Bandung National Institution of Technology (Itenas) Â  ABSTRAK Institusi pendidikan adalah tempat untuk melakukan penelitian dan inovasi untuk meningkatkan kualitas lingkungan yang mandiri. Penelitian ini bertujuan untuk menentukan besaran timbulan dan komposisi sampah dari institusi khususnya Institut Teknologi Nasional Bandung (Itenas). Metode sampling yang dilakukan berdasarkan SNI 19-3964-1994 dengan cara melakukan pengukuran timbulan dan komposisi sampah selama 8 hari berturut-turut. Berdasarkan hasil penelitian diperoleh rata-rata timbulan sampah Itenas sebesar 0,015 kg/m2/hari atau 0,156 kg/orang/hari dalam satuan berat dan 0,242 liter/m2/hari atau 2,446 liter/orang/hari dalam satuan volume. Komposisi sampah Itenas didominasi oleh sampah organik sebesar 50,78% yang terdiri dari sisa makanan dan dedaunan, sedangkan komposisi sampah lainnya antara lain 14,09% plastik; 4,54% kardus; 2,33% kertas; 1,93% kain; 1,21% kaca; 0,08% kaleng; 0,03% logam; dan 24,99% residu atau sampah lainnya. Kegiatan yang paling tinggi menghasilkan sampah organik di Itenas adalah kegiatan kantin sedangkan kegiatan Student Center (SC) menghasilkan sampah daur ulang yang paling tinggi. Kata kunci: sampah institusi, timbulan sampah, komposisi sampah, Institut Teknologi Nasional Bandung (Itenas)